Knowledge, attitude and practice regarding the use of dental operating microscope in pediatric dentistry in India: An online survey - Ferah Rehman; Gyanendra Kumar; Mridula Goswami (Journal of Oral Biology and Craniofacial Research)
Background and aim: Literature search shows scarcity of information regarding the use of Dental Operating Microscope (DOM) in children. There are various factors that limit the use of this novel technology by Pediatric Dentists in their practice. The aim of this study is to assess the knowledge, attitude and practice of pediatric dentist regarding DOM use in children. Method: The present study was a descriptive web based questionnaire study conducted among 363 Pediatric Dentists (PDs) of India. A close-ended questionnaire was prepared to test the KAP regarding microscope use among PDs. Results obtained were analyzed using descriptive analysis in SPSS software and correlation was studied using chi-square test where statistical significance was observed at p ​< ​0.05. Results: A response rate of 82.1% was observed. Majority (88.9%) of the pediatric dentists were aware of Dental operating Microscope (DOM) usage in their field, however, only 61.4% were aware of its magnification levels. 76.5% participants responded 12oclock position to be the ideal position. Majority (94.0%) agreed that DOM is helpful in locating canals in deciduous teeth. 70.5% think that DOM can increase apprehension of children. 85.2% believed that DOM can aid in behavior management of children through its live visual output. However, 84.2% of the pediatric dentists hadn’t used DOM in their practice. Conclusion: The knowledge, attitude and practice regarding dental operating microscope among pediatric dentists in India is limited. In the foreseeable future, the use of magnification is likely to become the standard of practice in dentistry.